THE MODERATING EFFECT OF FIRM SIZE ON THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE AND PROFITABILITY: INDONESIAN MANUFACTURING FIRMS (2020–2024) - Afifa Azka Putri; Erisa Aprilia Wicaksari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effect of capital structure on profitability and the moderating role of firm size in Indonesian manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. Employing a quantitative approach with purposive sampling, 102 companies with complete financial data were selected, yielding 510 observations. Profitability, measured by Return on Assets (ROA), Tobin’s Q, and Earnings Per Share (EPS), serves as the dependent variable, while capital structure, proxied by Debt to Asset Ratio (DAR) and Debt to Market Capitalization Ratio (DMCR), is the independent variable. Firm size is included as a moderator, and Annual Sales Growth (ASG) and Firm Age (FAGE) are control variables. Secondary data were obtained from company annual reports and Bloomberg, and analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) in EViews. The results show that DAR does not significantly affect profitability, while DMCR negatively and significantly affects ROA. Firm size moderates only the negative effect of DMCR on ROA, indicating that larger firms can better manage debt and reduce operational profitability risks. ASG positively affects ROA, and FAGE positively influences ROA but not Tobin’s Q or EPS. These findings provide insights into capital structure management, operational efficiency, and the strategic role of firm size.